2007
DOI: 10.1111/j.1365-2133.2006.07678.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrilysin (matrix metalloproteinase-7) in primary cutaneous and metastatic melanoma

Abstract: We found matrilysin expression in primary melanomas and in metastatic melanomas. We further demonstrated that the matrilysin IHC staining score was associated with invasive depth of primary melanoma lesions and metastases. Our observations indicate that matrilysin may be associated with melanoma progression, and may enhance melanoma tumour cell invasion. Therefore, matrilysin may be potentially valuable as a prognostic indicator to predict the clinical behaviour of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…Among a number of options, we focused on ADAM9, MMP7 and osteopontin (OPN) for their important role in melanoma progression [16], [18], [19]. Growth and dissemination of human melanoma require a cascade of cellular processes including cellular interactions and proteolytic cleavage of growth factor ligands and extracellular matrix proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among a number of options, we focused on ADAM9, MMP7 and osteopontin (OPN) for their important role in melanoma progression [16], [18], [19]. Growth and dissemination of human melanoma require a cascade of cellular processes including cellular interactions and proteolytic cleavage of growth factor ligands and extracellular matrix proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In melanoma ADAM9 protein expression is restricted to the cells within the invading front, being detectable in tumor cells and in peritumoral stromal fibroblasts, and absent in fibroblasts distal to the tumor site [15]. Expression studies in primary cutaneous and metastatic melanomas also revealed MMP7 association with tumor cell invasion and progression suggesting its prognostic value in predicting the clinical behavior of melanoma [16].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, MMP-1 overexpression conferred an invasive and metastatic phenotype on early stage melanoma cells, whereas MMP-1 downregulation in late stage melanoma cells curtailed metastasis and angiogenesis (43, 44). Similarly, MMP-7 overexpression is often found in prostate and skin cancer (4547) and may promote tumorigenesis by enhancing invasion, metastasis and cell proliferation (48–50). …”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical detection of MMP-7, therefore, may serve as a tissue marker for benign melanocytic lesions [59]. Spitz nevi are benign, acquired moles derived from melanocytes (pigment cells) and cause concern because they were often confused with melanoma.…”
Section: Diagnostic Markersmentioning
confidence: 99%